Analisis Kadar Timbal dan Gambaran Darah Gajah Sumatera (Elephas maximus sumatranus) di Pusat Latihan Gajah Sebanga Riau - Budiman, Hamdani; Azhar, Al; Yusuf, Irwandi (Jurnal Veteriner, 2010)
The aim of this research was to determine the lead concentration in blood and hematological profilesof Sumatran elephants. Eight out of 57 captivated Sumatran elephants in Sebanga Elephant TrainingCenter (ETC) Riau were examined for the lead concentration in the blood and for hematological profiles.The results showed that their lead concentration in blood was 0.3425 – 0.4633 ppm with the average of0.3905 ± 0.373 ppm. Their hemoglobin level was 9.60 – 12.10 g/dl with the average of 10.39 ± 1.20 g/dl.Hematocrit levels was 31 – 47% with the average of 37.50 ± 5.21%. In male, their average levels ofhemoglobin and hematocrit were 10.85 ± 1.28 g/dl and 41.00 ± 4.90%, respectively which were higher thanthose in female (9.93 ± 1.06 g/dl and 34.00 ± 2.53%, respectively). Their lead concentration was higher inthe younger elephant than in the older elephants. Although, the lead concentration in blood of Sumatranelephants was high, it appeared to be not related either with their hemoglobin or hematocrit levels. Therewas, however, relationship between the lead level in blood with the age of elephants.
Keywords: Lead, hemoglobin, hematocrit, Elephas maximus sumatranus